Implementation of Iso 9001, Iso 14001, Iso 45001 Requirements with the Systems of Electronic Document Turnover - P. Balabanov, Igor; F. Davletshin, Fail (International Journal of Engineering and Technology, 2018)
In the modern actively developing conditions of globalization and informatization of production, and emergence of new technologies, only those firms have chances to remain at the market which find ways and means of optimization of processes in time. Adhering to the basic principles of the integrated system of management ensures the most natural and trouble-free functioning of all organizational structure. This paper covers the specifics of work with documentation, or the system of paper and electronic document flow, and with the application of an electronic document management system taking into account observance of requirements of documentary information management system. Adherence to ISM requirements for documentary information management is quite real with options of conducting document flow. Nevertheless, it is much simpler and more effective to perform with already introduced EDMS, and the effect of its use of subjects is higher when the enterprise scale and a number of staff involved in work with documentation are bigger. The maximum output can be achieved from electronic document flow introduction with an optimum ratio of the functions demanded in operation and if opportunities of the chosen system correspond to them. Â Â